Flow characteristics of a large-size pressure-atomized spray using DTV. (September 2016) - Stevenin, C.; Tomas, S.; Vallet, A.; Amielh, M.; Anselmet, F.
Highlights: New Droplet Tracking Velocimetry (DTV) post-process is developed for complex dispersed phase (poly-dispersed & non-spherical) Our DTV post-process is associated with dedicated calibration to determine the Apparent Depth of Field of each droplet class DTV results reveal that this spray has a low radial dispersion combined with strong droplet turbulence anisotropy Droplet sizes strongly influence their dynamics: velocities and droplet sizes must effectively be measured simultaneously For droplet turbulence, estimated Cµ values (used in RANS models) are lower than those typically observed Abstract: The purpose of this study is to characterize the atomization of a jet of water sprayed into the air at high velocity through a commercial nozzle widely used for sprinkler irrigation. The typical diameter of the droplets present in the spray is in the range of several tens of micrometers to several millimeters. They are visualized by ombroscopy. A specific Droplet Tracking Velocimetry (DTV) technique is developed to estimate the size and velocity of these highly polydispersed droplets that are distinctly non spherical. This analysis is performed from the rupture of the liquid core region (about a distance of 550 nozzle diameters) to the dispersed zone (about a distance of 900 nozzle diameters). With this technique, we obtain joint size-velocity measurements that are rarely produced. Especially two velocity components and also a large diameter range are characterized at the same time; while with other techniques, such as Particle Doppler Anemometry (PDA), the diameter range is quite reduced and requires specific settings. Additional measurements of the liquid volume fraction are performed using a single mode fiber-optic probe. In the light of our experimental data, it appears that the turbulent droplet motion in the spray is strongly anisotropic. This anisotropy is quite unexpected because other studies on sprays (generally concerned with engine applications) show a relatively low anisotropy. We attribute this increase of anisotropy to the fact that, for this type of spray, the droplet relaxation time is long in comparison to the characteristic time of the turbulence and that biggest droplets are still submitted to atomization process. This strong anisotropy is responsible for the poor radial dispersion of the spray.